Activation of p38 MAPK Signaling‐Mediated Endoplasmic Reticulum Unfolded Protein Response by Nanopolystyrene Particles. Issue 4 (14th March 2019) - Qu, Man; Liu, Yaqi; Xu, Kangni; Wang, Dayong
Abstract: Nanopolystyrene particles have been widely used in many fields. However, the molecular responses of organisms to nanopolystyrene particles at predicted environmentally relevant concentrations are still largely unclear. Caenorhabditis elegans is employed herein to investigate the molecular response of p38 mitogen‐activated protein kinase (MAPK) signaling to nanoplastic particles (1 µg L −1 ) and the underlying molecular mechanism. In wild‐type nematodes, prolonged exposure (from L1‐larvae to adult day 3) to nanopolystyrene particles increases the expression of pmk‐1 encoding a p38 MAPK. Mutation of pmk‐1 induces a susceptibility to nanopolystyrene toxicity, suggesting that the p38 MAPK signaling mediates a protective response to nanopolystyrene particles. PMK‐1 functions in the intestine to act upstream of two transcriptional factors (ATF‐7 and SKN‐1), which can further act upstream of XBP‐1, a key regulator of endoplasmic reticulum unfolded protein response (ER UPR), to regulate the response to nanopolystyrene particles. PMK‐1, ATF‐7, SKN‐1, and XBP‐1 are all required for the induction of intestinal ER UPR in nematodes exposed to nanopolystyrene particles. Therefore, the intestinal p38 MAPK signaling may mediate a protective response to nanopolystyrene particles by activating XBP‐1‐mediated ER UPR. The results herein highlight the importance of molecular response in the intestine of organisms to nanopolystyrene particles. Abstract : The molecular responses of organisms to nanopolystyrene particles at predicted environmentally relevant concentrations are still largely unclear. In Caenorhabditis elegans, an intestinal p38 mitogen‐activated protein kinase signaling mediates a protective response to nanopolystyrene particles by activating XBP‐1‐mediated endoplasmic reticulum unfolded protein response. The results herein suggest the importance of intestinal response to nanopolystyrene particles in organisms.